The Influence of the Head of the Room Management Function on the Completeness of Nurse Documentation - Ching-Hui Chan; Shu Ju (An Idea Health Journal, 2025)
Nursing services have an important role in improving the quality of health services. The research design used in this study is a descriptive design with a cross sectional approach. The sample provisions were carried out by total sampling technique with a sample of 45 respondents. The data analysis used in this study was the statistical analysis of the T-test. The results showed that there was an influence between the management function of the head of the room on the completeness of the documentation of nurses in the inpatient room (p-value 0,001) <0,05. The conclusion of this study is that there is an influence between the management function of the head of the room on the completeness of the documentation of nurses. It is expected to improve the management function of the head of the room by attending training or seminars on work productivity and evaluating the completeness of nursing documentation on a regular basis.